Transformation of Character Education through PKn Learning in Elementary School Students in the Digital Era - Linda Tri Utami; Ari Wibowo (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the transformation of character education through civic education learning in elementary school students in the digital era. The research uses a qualitative approach with a descriptive method. Data was obtained through observations, interviews, and documentation carried out in the PKn learning process at SDN Karangmloko 1. The results of the study show that PKn learning has undergone a transformation from conventional learning to more contextual, interactive, and digital-based learning. The use of digital media such as learning videos, interactive media, and digital quizzes can increase students' active involvement in learning while helping students understand civic values and character. Second, the implementation of character education is carried out through the integration of the values of discipline, responsibility, cooperation, tolerance, honesty, and love for the homeland in learning activities and daily habits at school. Teachers play an important role as facilitators and role models in guiding students to use technology positively and responsibly. Third, the implementation of character education in the digital era also faces challenges, such as the limitation of teachers' ability to utilize technology, lack of supporting facilities, and the negative influence of the use of social media and gadgets on students. Therefore, cooperation between teachers, schools, and parents is needed in supporting the formation of students' character in the digital era. Thus, digital-based PKn learning has an important role in transforming the character education of elementary school students to become a generation that is intelligent, characterful, and wise in utilizing technology. Keywords: character education, civic learning, digital era, elementary school, learning transformation.